СЕМАНТИКА ПОСЕССИВНЫХ КОНСТРУКЦИЙ В МИРОВОСПРИЯТИИ РУССКИХ И АНГЛИЧАН (Philological Studies, 2019)
In this article the syntactic constructions уХ(есть)У and X has Y are regarded as a way of the possessivity category representation in the Russian and English world views. This universal cognitive category consists of three components: a possessor, an object and the possessive relation between them. In modern cognitive researches this category is modeled in the form of а frame. The central part of this frame is occupied by а subframe “properly possession”. All languages can be divided into BE-languages and HAVE-languages according to the main predicative way of “properly possession” representation. The Russian language belongs to BE-languages; the English language is a HAVElanguage. There are several meanings of possessivity that depend on the words semantics which fill in X and Y positions in the syntactic structures. The main meaning is ownership. According to A. Vezhbitskaya ethnosyntactic conception the principle of a sentence forming in a language is regarded the national world view. The objective form of a subject (the genitive case) and the verb быть point to passive and experience world view of the Russians (A. Vezhbitskaya’s term) and their nonactive attitude to possessions. The agentive form of a subject (the nominative / common case) and the verb have demonstrate agentive world view of the English culture representatives and their active attitude to possessions. These attitudes to possessions spread to the other possessivity meanings such as a subject characteristic, a subject states (physiological, psychological, and mental) and the meaning of an event in a subject’s life. The structure у Х (есть) У represents that a subject is not an active possessor of characteristic, state and he is “pushed aside” from taking part in an event. The structure X has Y demonstrates that a subject is an active possessor of characteristic, state and he plays the active role in an event. In general possessivity meanings that у Х (есть) У and X has Y represent coincide in the Russian and English languages. But the English structure has some additional meanings that are not represented by у Х (есть) У. These meanings are connected with location semantics. The meanings are a subject and an object colocation and an object presence in the space which has possessive relation with a subject. Representing these meanings the structure X has Y keeps active semantics of a subject.